Welded haunches for seismic retrofitting of bolted T-stub connections and flexural strengthening of simple connections. (15th December 2016) - Saberi, Hamid; Kheyroddin, Ali; Gerami, Mohsen
Highlights: Welded haunches as a way to rehabilitate T-stub bolted connections are tested. Making a moment connection from a pinned connection was evaluated using haunches. Compared the hysteretic responses of weak and rehabilitated connections. Investigated the failure modes of rehabilitated connections in experiments. Explored the energy dissipation capabilities from the hysteretic responses. Abstract: There are wide variety of techniques for seismic rehabilitation of structures. Selecting the optimum technique for rehabilitation of existing structures has been a challenge for engineers in the recent years. One of rehabilitation cases is to retrofit rigid connections in steel moment frames by making the least changes. Another case is rehabilitation of steel braced frames with pinned connections whose high relative displacements during an earthquake increase the collision probability for adjacent structures. In this paper, welded haunches as a technique for rehabilitation of bolted T-stub connections with weak bolts or weak T-stub flange as well as a technique for changing pinned connections to moment connections is experimentally investigated. Six corner connection specimens are made and tested under SAC cyclic loading protocol. The results of this study show that this rehabilitation technique not only modifies the cyclic behavior of weak rigid connections and changes simple bolted connections into moment connections, but also it improves the behavior of the rehabilitated connections in a way that their behavior is more desirable than that of the reference rigid connection designed according to AISC. For example, flexural capacity and rotational stiffness of the retrofitted connections are higher than those of the reference connection by 30 and 70% in average respectively. Furthermore, the connection failure potential in this rehabilitation technique is reduced by transferring the plastic hinge to the after-haunch area far from the connection area. The use of this rehabilitation technique in bolted connections with weak T-stub flange provides better cyclic behavior compared to that of a connection with weak bolts, since higher flexural capacity and energy dissipation is reached. The results show that this technique can be used for rehabilitation of adjacent simply braced frames without adequate separation distance to reduce the collision probability in earthquakes.